The influence of reflector on the thermal performance of single and double pass solar air heater: A comprehensive review. (2023) - Kashyap, Tanish; Thakur, Robin; Sethi, Muneesh; Tripathi, R.K.; Thakur, Abhishek; Kumar, Sushil; Kumar, Pawan; Goel, Bhaskar; Chand, Satish
Abstract: The collection and efficient utilization of solar radiations for various applications is extensively explored recently. Much advancement have been made in the thermal augmentation of single pass solar air heater (SP-SAH) and double pass solar air heaters (DP-SAH) using different techniques. The motive of this article is to represent a compressive literature review on most recent evolution stated in the field of SP-SAH and DP-SAH with reflectors. Numerous designs of reflectors viz, Flat plate, Linear Fresnel, Compound Parabolic Concentrator (CPC), Truncated CPC, V-groove secondary reflector etc. which have been utilized to enhance energy input to the SP-SAH and DP-SAH are reviewed in this work. Studies on the impact of reflectors on the performance of SAH and their major findings are discussed in the present article.